(3GdCOhjI GdeQcHI HMSH GdehGVY GdBdeIs - (3LGdjfhSs ((3Ydi Hf eMeO Hf CMeO GdCROi GdbGQLi s)
(3ChdgG (B:s
(3eHJhQ GdChd , hjHOC GdehLhO efg CKfGA GdebGdI GdNGeSI Hbhdg (B: (3Cf jZSd aeg HTQGHg s
(3BNQgG (B:s
(3eHJhQ CjVkG , hBNQ eG ajg CKfGA GdebGdI GdYGTQI (B_ (3hgj BNQ GdebGdGJ(B: (3JGNP fHJG jGHSG aJMQbg hJSMbg hJNdW eY QeGOg TjFG ef SfHd hJYLfg HYSd hJSJYedg aEfg jbHV GddKI s
(3Vef eLehY , JQJjHgG (B: (3ef U (B84 - (3U(B183s
(3bhHdJ Ydi fSNI cJHJ SfI (B430(3g`s
(3jHOC GdehLhO ajg ai GdebGdI GdNGeSIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B6 s
Keywords: (3GdWHs